2018
DOI: 10.1186/s13052-018-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens?

Abstract: BackgroundThe simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess.Case reportWe report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…He was found to have karyotype 47XXY, and a post hoc molecular analysis showed that a pathogenic variant in HSD3B2 and not CYP21A2 was the cause of the disease. The association of Klinefelter syndrome and CAH is extremely rare, with very few cases reported in the literature [ [39] , [40] , [41] ]. More details of this case will be presented in a future manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…He was found to have karyotype 47XXY, and a post hoc molecular analysis showed that a pathogenic variant in HSD3B2 and not CYP21A2 was the cause of the disease. The association of Klinefelter syndrome and CAH is extremely rare, with very few cases reported in the literature [ [39] , [40] , [41] ]. More details of this case will be presented in a future manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with appropriately treated CAH exhibit normal cognitive and executive function ( Parker et al, 2006 ; Messina et al, 2020a ). However, parental reports indicate increased social problems on the Childhood Behavior Checklist ( Zanella et al, 2018 ; Messina et al, 2020b ). This may happen in 47,XXY as well, so we wondered how the potential mitigation of a supernumerary X with CAH could affect this aspect.…”
Section: Discussionmentioning
confidence: 99%
“… Parker et al (2006) reported a boy with positive newborn screening of CAH and later diagnosis of 48,XXXY/47, XXY mosaicism after concerning physical exam that included poor weight gain, microcephaly, and mild developmental delay. Another study reported a boy who was diagnosed with CAH at 2 years old but evaded evaluation for 47,XXY until he was 18 years old, primarily due to low testicular volume ( Zanella et al, 2018 ). We present a case of a young male with the salt-wasting phenotype of caused by 21OHD CAH and 47,XXY.…”
Section: Introductionmentioning
confidence: 99%
“…So, we can speculate that high adrenal androgen secretion by CAH had a greater relevance than the low testicular androgen production, typical of KS. Till now there are 5 reported cases of co-occurrence of KS with CAH, one of them had 3BHSD2 deficiency but with a different presentation and the rest of them had 21-OH deficiency ( 23 , 24 , 25 , 26 , 27 ). Four of them were detected in boys and another one in a 51-year-old male.…”
Section: Discussionmentioning
confidence: 99%